N-carbamylglutamate supplementation improves laying performance of layers by regulating hypothalamic-pituitary-ovarian axis - Peng, Xiao-Bing; Wang, Qing-Yue; Zhang, Yan; Liu, Na; Ma, Wei; Wang, Chun-Qiang (Frontiers in Veterinary Science, 2025)
This study aimed to investigate the effects of dietary supplementation of N-carbamylglutamate (NCG) on the laying performance of layers and explore the underlying endocrine mechanism involving the hypothalamic-pituitary-ovarian (HPO) axis. Ninety-six 12-week-old layers of the Zhuanghe Dagu breed were divided into two groups: CON and TRT, with four replicates and 12 birds per replicate. The experimental period lasted 24 weeks, during which the CON group received a basal diet while the TRT group received a basal diet supplemented with 0.12% NCG. The results showed that NCG supplementation in the diet resulted in an increase in the egg production rate and an advancement in the timing of egg-laying compared to the CON group. To gain insights into the underlying molecular mechanisms, transcriptomics analysis was conducted on the hypothalamus, pituitary, and ovary. Differential gene expression analysis identified 156 differentially expressed genes (DEGs) in the hypothalamus, 208 DEGs in the pituitary, and 229 DEGs in the ovary. Pathway analysis revealed that these DEGs were enriched in 2 pathways in the hypothalamus, 8 pathways in the pituitary, and 9 pathways in the ovary, all of which are related to reproduction. Of particular interest, the expression of specific genes involved in the HPO axis, such as FSHB and GNRH1 in the hypothalamus, DHH and GNRHR in the pituitary, and RSPO1, ZP3, GSTA3, C14orf39, HOXA10, and IRX5 in the ovary, was significantly regulated by NCG supplementation. These findings were further validated by quantitative real-time polymerase chain reaction, which confirmed the expression profiles of the aforementioned genes observed in the RNA-seq results. Overall, these findings provide valuable insights into the endocrine mechanisms underlying the improvement of laying performance in layers through NCG supplementation.